TINJAUAN PAJAK DAERAH DAN PDRB ATAS EFEKTIVITAS DAN KONTRIBUSINYA TERHADAP PAD KOTA MADIUN - Norman Sitinjak (Ma Chung Press, 2016)
Local Tax highly expected to be a main pillar Local Revenue. For that Local Government must alwaysstrive to improve Local Tax . Excavation and development of the existing potential should always bedone . To improve compliance and awareness of citizens on Local Taxes , Government of the City ofMadiun also should always do a socialization especially about role society in development throughlocal taxes